Prenatal hypoxia induces increased cardiac contractility on a background of decreased capillary density - Ousley Victoria; Hauton David (BMC Cardiovascular Disorders, 2009)
Abstract Background Chronic hypoxia in utero (CHU) is one of the most common insults to fetal development and may be associated with poor cardiac recovery from ischaemia-reperfusion injury, yet the effects on normal cardiac mechanical performance are poorly understood. Methods Pregnant female wistar rats were exposed to hypoxia (12% oxygen, balance nitrogen) for days 10–20 of pregnancy. Pups were born into normal room air and weaned normally. At 10 weeks of age, hearts were excised under anaesthesia and underwent retrograde 'Langendorff' perfusion. Mechanical performance was measured at constant filling pressure (100 cm H2O) with intraventricular balloon. Left ventricular free wall was dissected away and capillary density estimated following alkaline phosphatase staining. Expression of SERCA2a and Nitric Oxide Synthases (NOS) proteins were estimated by immunoblotting. Results CHU significantly increased body mass (P < 0.001) compared with age-matched control rats but was without effect on relative cardiac mass. For incremental increases in left ventricular balloon volume, diastolic pressure was preserved. However, systolic pressure was significantly greater following CHU for balloon volume = 50 μl (P < 0.01) and up to 200 μl (P < 0.05). For higher balloon volumes systolic pressure was not significantly different from control. Developed pressures were correspondingly increased relative to controls for balloon volumes up to 250 μl (P < 0.05). Left ventricular free wall capillary density was significantly decreased in both epicardium (18%; P < 0.05) and endocardium (11%; P < 0.05) despite preserved coronary flow. Western blot analysis revealed no change to the expression of SERCA2a or nNOS but immuno-detectable eNOS protein was significantly decreased (P < 0.001) in cardiac tissue following chronic hypoxia in utero. Conclusion These data offer potential mechanisms for poor recovery following ischaemia, including decreased coronary flow reserve and impaired angiogenesis with subsequent detrimental effects of post-natal cardiac performance.